The influence of nitric oxide synthase 2 on cutaneous wound angiogenesis - Chin, L. C.; Kumar, P.; Palmer, J. A.; Rophael, J. A.; Dolderer, Jürgen H.; Thomas, G. P.L.; Morrison, W. A.; Penington, A. J.; Stewart, A. G.; Mitchell, G. M. (British Journal of Dermatology, 2011)
Background Inducible nitric oxide synthase (nitric oxide synthase 2, NOS 2) inhibition significantly suppresses chronically ischaemic skin flap survival, possibly because of reduced angiogenesis. Objectives To investigate the effect of genetic NOS 2 inhibition on cutaneous wound angiogenesis in two in vivo murine models. The impact of NOS 2 manipulation on vascular endothelial growth factor (VEGF)-A stimulated and fibroblast growth factor (FGF)-2 stimulated angiogenesis was also investigated in the Matrigel ® plug assay. Methods (i) Matrigel plugs/incisional wounds: two groups of NOS 2-/- mice and two groups of wild-type (WT) mice had bilateral Matrigel plugs containing 500 ng mL -1 VEGF-A or 1000 ng mL -1 FGF-2 injected subcutaneously in the abdomen. A 2·5 cm long dorsal incisional skin wound was created and sutured closed in the same animals. Wounds and plugs were explored at 7 or 12 days. (ii) Excisional wounds: dorsal 0·5 × 1·0 cm excisional skin wounds were created in four groups (two NOS 2-/- and two WT) and explored at 7 or 14 days. Wounds and Matrigel plugs were examined histologically and morphometrically for determination of percentage vascular volume (PVV). Results The PVV in NOS 2-/- incisional wounds and excisional wounds was significantly less than in WT wounds (P = 0·05 and P < 0·001, respectively). The PVV was significantly less in VEGF-A stimulated Matrigel plugs compared with FGF-2 stimulated plugs in NOS 2-/- mice (P < 0·01), but not in WT mice. Conclusions NOS 2 is significantly involved in angiogenic signalling in healing skin wounds, particularly within the first 7 days. However, Matrigel plug vascularization suggests that the role of NOS 2 in angiogenesis is related to VEGF-A but not FGF-2 stimulated angiogenesis. © 2011 British Association of Dermatologists.
CRIS-Team Scopus Importer:2024-12-11